The Effect of Intravenously Injected Adenosine Diphosphate in Rat and Rabbit - Bosshardt, D. K; Howe, E. E (Thrombosis and Haemostasis, 1969)
Very large quantities of ADP injected intravenously into rats and rabbits were found to disappear within a matter of minutes. Dietary changes which favor thrombus pro duction did not alter this capacity for ADP elimination. It seems unlikely that varia tions in circulating ‘ADPase’ are involved in thrombus formation.